Lactobacillus rhamnosus GG modulates intestinal mucosal barrier and inflammation in mice following combined dietary exposure to deoxynivalenol and zearalenone. (April 2016) - Wan, Murphy L.Y.; Turner, Paul C.; Allen, Kevin J.; El-Nezami, Hani
Highlights: LGG conferred protection against DON/ZEA by regulation of MUC2 and intestinal TFF3. LGG improved DON/ZEA-induced plasmad -lactate and IL8/CXCL8 levels. LGG improved DON/ZEA-induced serum IgA, IgM and IgG dysregulation. LGG partially prevented or treated the unwanted adverse effects of DON/ZEA. Abstract: Deoxynivalenol (DON) and zearalenone (ZEA) are mycotoxins produced by Fusarium species, which naturally co-occur in foods/feeds. The gastrointestinal tract represents the first barrier against dietary xenobiotics. The present study aimed to investigate the ability of Lactobacillus rhamnosus GG (LGG) to improve intestinal barrier functions and ameliorate inflammation in Balb/c mice fed diets containing DON/ZEA mix. An exposure regimen that simulated human exposure experience was designed. Chronic ingestion of DON/ZEA mix regulated goblet cell mucus secretion in cooperation with intestinal trefoil factors, accompanied by a moderate increase in plasmad -lactate level. Plasma IL8/CXCL8 and serum immunoglobulin (Ig)A, IgM and IgG levels were also differentially regulated. The results showed that LGG partially prevented or treated the unwanted adverse effects of DON/ZEA in mice by regulation of goblet cell mucus secretion, improvement of plasmad -lactate, IL-8/CXCL8 and serum Ig levels. This offers a potential dietary intervention strategy against intestinal exposure to mycotoxins.